Comparative Assessment of uNGAL, uNAG and Cystatin C As Early Biomarkers in Renal Post-Transplant Patients - G. Nikolov; M. Boncheva; T. Gruev; K T Trajkovska; I. Kostovska (Walter de Gruyter GmbH, 2018)
Urinary neutrophil gelatinase-associated lipocalin (uNGAL), urinary N-acetyl-b-d-glucosaminidase (NAG), urinary α1-microglobulin/creatinine ratio and cystatin C have been suggested as potential early markers of delayed graft function (DGF) following kidney transplantation. We conducted a prospective study in 50 consecutive kidney transplant recipients to evaluate serial changes of these biomarkers within the fi rst week after trans-plantation and assess their performance in predicting DGF (dialysis requirement during initial post-transplant week) and graft function throughout the fi rst year. Urine samples were collected on post-transplantation days 0, 1, 2, 4, and 7. Statistical analysis: Linear mixed and multivariable regression models, receiver-operating characteristic (ROC), and areas under ROC curves were used. At all-time points, mean urinary NGAL levels were signifi cantly higher in patients developing DGF. Shortly after transplantation (3-6 h), uNGAL and uNAG values were higher in DGF recipients (on average +242 ng/mL; NAG  6.8 U/mmol creatinine, considering mean dialysis time of 4.1 years) and rose further in the fol-lowing days, contrasting with prompt function recipients. On Day-1 uNGAL levels accu-rately predicted DGF (AUC-ROC = 0.93), with a performance higher than serum creatinine (AUC-ROC = 0.76), and similar to cystatin C (AUC-ROC = 0.95). Multivariable analyses revealed that uNGAL levels at days 4 and 7 were strongly associated with one-year serum creatinine level. Urinary NGAL, serum cystatin C is an early marker of graft injury and is independently associated with dialysis requirement within one week after transplantation and one-year graft function.